2022
DOI: 10.3389/fmicb.2022.878387
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Abiotic and Biotic Mechanisms of Pyrite Reduction

Abstract: Pyrite (FeS2) has a very low solubility and therefore has historically been considered a sink for iron (Fe) and sulfur (S) and unavailable to biology in the absence of oxygen and oxidative weathering. Anaerobic methanogens were recently shown to reduce FeS2 and assimilate Fe and S reduction products to meet nutrient demands. However, the mechanism of FeS2 mineral reduction and the forms of Fe and S assimilated by methanogens remained unclear. Thermodynamic calculations described herein indicate that H2 at aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 74 publications
(131 reference statements)
1
36
1
Order By: Relevance
“…Intriguing recent studies of the methanogens Methanococcus voltae (Methanococcales) and Methanosarcina barkeri (Methanosarcinales) showed that they can reductively dissolve FeS 2 and use dissolution products to meet Fe and S demands (Payne et al, 2021;Spietz, Payne, Kulkarni, et al, 2022b). Methanococcus voltae encodes a SUF-minimal pathway lacking a homologue of cysteine desulfurase whereas M. barkeri encodes a traditional SUF pathway with a homologue of cysteine desulfurase (Johnson et al, 2021).…”
Section: Iron Sulfur-based Metallocofactorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intriguing recent studies of the methanogens Methanococcus voltae (Methanococcales) and Methanosarcina barkeri (Methanosarcinales) showed that they can reductively dissolve FeS 2 and use dissolution products to meet Fe and S demands (Payne et al, 2021;Spietz, Payne, Kulkarni, et al, 2022b). Methanococcus voltae encodes a SUF-minimal pathway lacking a homologue of cysteine desulfurase whereas M. barkeri encodes a traditional SUF pathway with a homologue of cysteine desulfurase (Johnson et al, 2021).…”
Section: Iron Sulfur-based Metallocofactorsmentioning
confidence: 99%
“…Recent studies that showed FeS (aq) clusters are made available through FeS 2 reduction (Payne et al, 2021; Spietz, Payne, Kulkarni, et al, 2022b) and are likely neutrally charged at circumneutral pH (Rickard & Luther, 2007). FeS (aq) are likely to be directly assimilated by methanogens, which provides a new avenue to begin to explore questions of how such a transition between abiotic catalysis and biotic catalysis might have taken place.…”
Section: Iron Sulfur‐based Metallocofactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several recent studies have shown that FeS 2(p) can be reductively dissolved through both abiotic and biotic processes at anoxic, physiological conditions 5 . For the former, dissolved hydrogen gas in micromolar concentrations and at biologically relevant temperatures (approximately 40°C) can abiotically reduce FeS 2(p) , resulting in what has been hypothesized to be a pyrrhotite (Fe 1‐x S (p) ) surface‐associated phase and release of HS − (aq) into solution 6 . For the latter, methanogens as anaerobic archaea generating methane via metabolism of carbon dioxide, alcohols, and organic acids, 7 were also shown to reduce FeS 2(p) 8–13 .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism and cellular pathways responsible for this process have yet to be elucidated. Recent transcriptomics work on Methanosarcina barkeri cultured in the presence of different Fe/S sources implicates alpha-keto reductases, a flavin mononucleotide-dependent flavodoxin reductase, and hydrolases as putative enzymes involved in FeS 2 reduction ( 21 ). Our previous work with M. voltae showed that cells grown on FeS 2 are smaller and may use an IssA protein to sequester iron as a thioferrate-like species ( 20 ).…”
Section: Introductionmentioning
confidence: 99%